2020
DOI: 10.1051/e3sconf/202020215014
|View full text |Cite
|
Sign up to set email alerts
|

Information Anxieties and Information Distrust: The effects of Overload Information about COVID – 19

Abstract: Covid-19 is the world's main focus, so the mass media is competing to provide details information. The amount of information related to Covid-19 in the communities raises information overload. The purpose of the study is to know the effects of overload information about Covid-19 on the information of anxiety and distrust of information about the people of Semarang. This research uses quantitative methods. The samples in this study were one hundred and fifty seven respondents which is acquired using random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The correct information is usually not able to be filtered out by the layperson, and therefore, it is more than likely that someone would believe the information found online to be valid. 39 Anxiety and panic can also induce the recirculation of misinformation online, especially regarding preventive measures against COVID-19, which includes natural remedies. 39 It is possible that some information on natural remedies were presented as medical information and were wrongly perceived as actual information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct information is usually not able to be filtered out by the layperson, and therefore, it is more than likely that someone would believe the information found online to be valid. 39 Anxiety and panic can also induce the recirculation of misinformation online, especially regarding preventive measures against COVID-19, which includes natural remedies. 39 It is possible that some information on natural remedies were presented as medical information and were wrongly perceived as actual information.…”
Section: Discussionmentioning
confidence: 99%
“…39 Anxiety and panic can also induce the recirculation of misinformation online, especially regarding preventive measures against COVID-19, which includes natural remedies. 39 It is possible that some information on natural remedies were presented as medical information and were wrongly perceived as actual information. The general public might have considered that performing these suggestions would not yield a negative result, and would not be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…, 2021), China (Song et al. , 2021), Indonesia (Isyawati Permata Ganggi, 2020) and the United Kingdom suggest that psychological well-being and mental health are negatively influenced by information overload (Liu et al. , 2021) and that information anxiety led to information avoidance during COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of use and specific information source selection can be instrumental to increasing the intensity of the stressors, strain and outcome. Literature published during COVID-19 confirmed that information exposure leads to information overload, information anxiety and information avoidance behavior Song et al, 2021;Isyawati Permata Ganggi, 2020;Liu et al, 2021). The more frequently individuals are exposed to one or more of these information sources, the more chances they have to experience information overload, information anxiety and information avoidance behavior (Azad, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, they can take the time to evaluate all necessary switching costs and not feel pressured to delay their booking decisions. This can be explained by the effect of consumer psychological laziness, which can be stimulated when sufficient time is given to review overwhelming information (Ganggi, 2020) and to make their final decisions rather than to defer.…”
Section: Discussion and Conclusion Conclusionmentioning
confidence: 99%